POLA PERTUMBUHAN RAGI TAPE PADA FERMENTASI KULIT SINGKONG - Darimiyya hidayati; Darratul Ba’ido; Sri Hastuti (AGROINTEK, 2013)
Cassava peel is plenty agriculture residu because many food product use cassava asraw material, especially in Madura. The use of cassava peel is limited because of high cynideacid, low glucose, and low protein. The result of the first experiment shows that ragi tape is thethe most suitable ragi for fermentation cassava peel. The objective of this research is todetermine optimum fermentation time for cassave peel using ragi tape. The experiment havedone in laboratorium TIP UTM. Cassava peel fermented using 5% ragi tape until 9 days.Parameter of this experiment ar HCN content, protein, pH, and growth of ragi. The resultshows that optimum fermentation time is 6 days